Riparian Tree Vegetation Diversity Salah Nama Island in Banyuasin, South Sumatera - Mirna Dwirastina; Etty Riani; Agnes Puspita Sudarmo (Faculty of Fisheries and Marine Universitas Airlangga, 2021)
Highlight Research:Riparian plants play an important role in maintaining the balance of an aquatic ecosystem.The diversity of riparian aquatic plants on the island of Salah Nama BanyuasinData collection on riparian plants used the quadratic transect methodThe results showed that there were 21 types of riparian aquatic plants in 16 families.The highest composition is in the Lythraceae family, namely Sonneratia acidaAbstractRiparian plants play an important role in maintaining the balance of an aquatic ecosystem. The missing plant components from a water can cause sedimentation and change the microhabitat in these waters. The purpose of the study is to determine the diversity of riparian aquatic plants on the island of Salah Nama Banyuasin. The research was conducted in August 2016, November 2016, and January 2017 at Salah Nama Island Mariana Ilir Banyuasin 1, South Sumatra. Sampling was done by using the purposive sampling method. Determination of the sampling location used GPS (Global positioning system). Observation stations consisted of 5 sampling locations. The method of taking water plants was done in exploratory way. Data collection on riparian plants used the quadratic transect method measuring 1 m x 1 m. Samples of riparian plants were taken then wrapped with newspaper or paper and put into large plastic, labeled then taken to the testing laboratory Institute Inland fisheries and extension, Palembang. The results showed that there were 21 types of riparian aquatic plants in 16 families. The highest composition is in the Lythraceae family, namely Sonneratia acida. The diversity index of aquatic plants ranges from 1 <H'<3 in the stable condition category. Based on the results of the study, the riparian plant species that dominated the most were Sonneratia sp. The conclusion that can be drawn is that the diversity of riparian plants on the island of Salah Nama is in the medium category, the dominant riparian plants are Sonneratia sp.